Consumer Behavior Prediction and Enterprise Precision Marketing Strategy Based on Deep Learning - Yuan, Zhe (Informatica, 2024)
This paper discusses the consumer behavior prediction and enterprise precision marketing strategy based on deep learning. This paper introduces the research on consumer behavior prediction and emphasizes the advantages of LSTM network in processing time series data. The method of data collection and prepossessing is introduced, and LSTM model is constructed to show its prediction ability through data. Results The predictive accuracy of the model was evaluated, and the effects of different marketing strategies were analyzed by key indicators. Develop a comprehensive marketing strategy that includes personalized recommendations, limited-time offers, member rewards, checkout process optimization, and social media engagement. Deep learning technology can effectively improve the prediction accuracy of consumer behavior, provide a scientific basis for enterprises to achieve precision marketing, and help enterprises to improve market competitiveness and customer satisfaction.